PENGARUH VARIASI BERAT KATUP BUANG DAN KETINGGIAN INPUT PADA KINERJA POMPA HIDRAM - Denilson Denilson; Deny Murdianto; Sudirman Sudirman (Jurnal Borneo Saintek, 2022)
The hydram pump comes from the word Hydraulic Ram, which is a pump that works by relying on the beat of a hydraulic system that can work without using electricity or fuel. Hydram pumps work by harnessing the potential energy in water in a straight pipe and then turning it into dynamic pressure which results in the creation of a water strike resulting in high pressure in the pump. The purpose of this study was to determine the effect of variations in exhaust valve weight and input height on the performance of the hydram pump. The exhaust valve weight variables used in this study were 0 gram, 40 gram, 50 gram and 60 gram, with the input height from the surface of 190 cm and 240 cm. The analysis technique is carried out by examining the data obtained from the research results, where the results are in the form of quantitative data made in tabular form and displayed in graphical form. The results of the study showed the highest efficiency of 52.47% at a height of 240 cm, and at a height of 190 cm the highest efficiency was obtained at 40.75%, and the highest yield water discharge at a valve weight of 50 grams was 6.51 l/minute at a height of 240 cm. and at a height of 190 cm, the resulting water discharge is 3.80 l/minute with a valve weight of 50 grams.